The Pathogenic Features of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): Possible Mechanisms for Immune Evasion? - Wang, Zhihui; Zhou, Ming; Fu, Zhenfang; Zhao, Ling (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is a newly emerging, highly transmitted and pathogenic coronavirus that has caused global public health events and economic crises. As of March 4, 2021, more than 100 million people have been infected, more than 2 million deaths have been reported worldwide, and the numbers are continuing to rise. To date, a specific drug for this lethal virus has not been developed to date, and very little is currently known about the immune evasion mechanisms of SARS-CoV-2. The aim of this review was to summarize and sort dozens of published studies on PubMed to explore the pathogenic features of SARS-CoV-2, as well as the possible immune escape mechanisms of this virus.